2015
DOI: 10.1371/journal.pone.0142425
|View full text |Cite
|
Sign up to set email alerts
|

Drug Susceptibility Patterns in MDR-TB Patients: Challenges for Future Regimen Design. A Cross-Sectional Study

Abstract: Globally, there is substantial concern regarding the challenges of treating complex drug resistance patterns in multidrug resistant tuberculosis cases. Utilising data from three different settings (Estonia, Latvia, Romania) we sought to contrast drug susceptibility profiles for multidrug resistant tuberculosis cases, highlight the difficulties in designing universal regimen, and inform future regimen selection. Demographic and microbiological surveillance data for multidrug resistant tuberculosis cases from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In one study conducted in Estonia and Latvia, findings were different as for the association between previous pyrazinamide usage and pyrazinamide resistance. In Estonia, the rates of resistance to pyrazinamide showed no difference between new and previously treated cases, whereas in Latvia, pyrazinamide resistance was higher in new cases than in previously treated cases [24]. Our present study also showed that there was no difference between pyrazinamide resistance in new cases versus in the previously treated cases.…”
Section: Discussionsupporting
confidence: 47%
“…In one study conducted in Estonia and Latvia, findings were different as for the association between previous pyrazinamide usage and pyrazinamide resistance. In Estonia, the rates of resistance to pyrazinamide showed no difference between new and previously treated cases, whereas in Latvia, pyrazinamide resistance was higher in new cases than in previously treated cases [24]. Our present study also showed that there was no difference between pyrazinamide resistance in new cases versus in the previously treated cases.…”
Section: Discussionsupporting
confidence: 47%
“…We examined the impact of time to initiation of any MDR TB treatment regimen rather than a regimen tailored to second-line drug sensitivity testing. Given known high levels of additional drug resistance in MDR TB patients in Latvia, it is probable that many patients included in this study had their treatment regimen subsequently altered, which is not captured here and could be the subject of future research ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 99% of new cases and 86% of re-treatment cases were reported by the World Health Organization to have been tested phenotypically or genotypically for rifampin-resistant or MDR TB in 2014; the 86% reflects clinical use of prior drug-susceptibility results for re-treatment cases. All MDR TB cases were tested for resistance to second-line drugs in 2013 ( 14 ). Access to MDR TB treatment is universal in Latvia.…”
mentioning
confidence: 99%
“…In our previous survey, PZA resistance was 2% in 171 non-MDR-TB cases (unpublished data). This survey revealed that the rate of resistance to PZA was 33.3% (95% CI 28.1–38.5) in MDR-TB cases, which is relatively low compared to 48.8% (95% CI 30.1–67.5%) in the western Pacific, where Taiwan is located [14], and compared to Baltic countries, such as Estonia (71.4%) and Latvia (75.0%) [15]. However, in Estonia, rates of resistance to PZA showed no difference between new (71.4%) and previously treated cases (71.4%), and in Latvia, PZA resistance was higher in new cases (75.0%) than in previously treated cases (69.2%) [14].…”
Section: Discussionmentioning
confidence: 99%